God’s creative breath according to Ibn ’Arabî: An andalusian example of harmony between faith, mysticism and philosophy - Flaquer, Jaume (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Ibn ´Arabî (1165-1240) was responsible for systematizing Sufi thought, in which Neoplatonic philosophy is harmonized with elements of medieval astrological science, with Islamic mysticism, and with faith in Creation and the in Transcendence of God. Gnosticism and Docetism are also present in Ibn ´Arabî’s mysticism. He shares with other Sufis the notion that Oneness of Being is manifested and deployed in the Plurality of Creation. The concept of Divine Breath makes belief in Creation and the doctrine of Emanation compatible. All things are considered Words of God. Jesus becomes a paradigm of all Creation because he is the «embodiment» of the Merciful Breath exhaled over Mary by the angel Gabriel